2020
DOI: 10.1063/5.0034874
|View full text |Cite
|
Sign up to set email alerts
|

Effects of space sizes on the dispersion of cough-generated droplets from a walking person

Abstract: The dispersion of viral droplets plays a key role in the transmission of COVID-19. In this work, we analyze the dispersion of cough-generated droplets in the wake of a walking person for different space sizes. The air flow is simulated by solving the Reynolds-averaged Navier–Stokes equations, and the droplets are modeled as passive Lagrangian particles. Simulation results show that the cloud of droplets locates around and below the waist height of the manikin after 2 s from coughing, which indicates that kids … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
26
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 52 publications
(26 citation statements)
references
References 19 publications
0
26
0
Order By: Relevance
“…5,6 Researchers have sought to examine the scientific underpinning of these guidelines by investigating the underlying physics of respiratory events and transport mechanisms that contribute to the propagation of pathogen-carrying saliva droplets. 6–23 For example, Yang and co-workers 7,8 used a one-way Eulerian–Lagrangian framework to investigate saliva particle transport from a moving person in various situations. Bourouiba et al (2014), 20 and more recently, Leung et al (2020), 17 Fischer et al (2020), 18 and Verma et al (2020) 19 investigated experimentally indoor coughing and sneezing expiratory events and reported that saliva particles of such events could, under certain conditions, propagate as far as 7–8 m away from the person.…”
Section: Introductionmentioning
confidence: 99%
“…5,6 Researchers have sought to examine the scientific underpinning of these guidelines by investigating the underlying physics of respiratory events and transport mechanisms that contribute to the propagation of pathogen-carrying saliva droplets. 6–23 For example, Yang and co-workers 7,8 used a one-way Eulerian–Lagrangian framework to investigate saliva particle transport from a moving person in various situations. Bourouiba et al (2014), 20 and more recently, Leung et al (2020), 17 Fischer et al (2020), 18 and Verma et al (2020) 19 investigated experimentally indoor coughing and sneezing expiratory events and reported that saliva particles of such events could, under certain conditions, propagate as far as 7–8 m away from the person.…”
Section: Introductionmentioning
confidence: 99%
“…Droplet dispersion during coughing by people who are walking plays an important role in the transmission of COVID-19. A simulation showed that droplets in the air in a narrow space, such as a hallway, were transmitted below waist height (of the emitter) [28]. Wake measurements confirmed that the speed and distribution stabilized as the distance from the mobile slipstream at chest and waist height increased.…”
Section: Conclusion and Discussionmentioning
confidence: 92%
“…Such aerosol clouds include various types of cells (e.g., epithelial cells and leukocytes), ions present in mucus and saliva (e.g., Na , K , and Cl−), and, potentially, various infectious agents suspended in the droplets (e.g., bacteria, fungi, and viruses). Even weak air currents caused by innocuous daily activities, such as walking 7 or opening doors, can transport these infectious droplets over long distances ( ). Such airborne transmission is the primary driver for virus spread in indoor spaces such as bathrooms, doctor’s offices, daycare centers, and public transportation; it is also important in many outdoor environments 8 .…”
Section: Introductionmentioning
confidence: 99%